The international geography of general purpose technologies (GPTs) and internationalisation of corporate technological innovation. Issue 1 (2nd January 2018) - Qiu, Ranfeng; Cantwell, John
Abstract: This study is inspired by a discussion that there is a shift towards more internationalised innovation networks in multinational corporations. In this study, we introduce the concept of general purpose technologies (GPTs) and examine the role of GPTs in the internationalisation of innovation activities. Based on an U.S. Patent and Trademark Office database covering patents granted in the U.S. to large MNCs between 1969 and 1995, our empirical findings suggest that the development of GPTs is closely linked to the internationalisation of corporate innovations. Moreover, the internationalisation of GPTs is significantly associated with the level of centrality of GPTs within an industry. GPTs are more likely to be generated in an innovating firm's foreign countries when they serve as the non-primary technologies in an industry. More importantly, a shift in the creations of GPTs to foreign countries is accompanied with increasingly more innovations in an industry's primary technology areas being moved to host countries.